Postbiotics in rheumatoid arthritis: emerging mechanisms and intervention perspectives - Ying, Zhen-Hua; Mao, Cheng-Liang; Xie, Wei; Yu, Chen-Huan (Frontiers in Microbiology, 2023)
Rheumatoid arthritis (RA) is a prevalent chronic autoimmune disease that affects individuals of all age groups. Recently, the association between RA and the gut microbiome has led to the investigation of postbiotics as potential therapeutic strategies. Postbiotics refer to inactivated microbial cells, cellular components, or their metabolites that are specifically intended for the microbiota. Postbiotics not only profoundly influence the occurrence and development of RA, but they also mediate various inflammatory pathways, immune processes, and bone metabolism. Although they offer a variety of mechanisms and may even be superior to more conventional "biotics" such as probiotics and prebiotics, research on their efficacy and clinical significance in RA with disruptions to the intestinal microbiota remains limited. In this review, we provide an overview of the concept of postbiotics and summarize the current knowledge regarding postbiotics and their potential use in RA therapy. Postbiotics show potential as a viable adjunctive therapy option for RA.